Cranium Bifidum with Meningo-encephalocele in a Haryana calf – A Case Report - Kumar, Rahul; Gangwar, Neeraj K.; kumar, Prabhakar (Indian Journal of Veterinary Anatomy, 2018)
The calf presented with inability to stand and defect in calvaria with a large sac like protrusion measuring 7.5x3 cm on dorso-cranial aspect of the cranium, filled with approximately 150 ml of fluctuating fluid. The protruded sac was not covered by skin. Fluid from the sac was drained out and examined; it was clear with few stains of blood resembling cerebrospinal fluid. The calf was hypothermic. The calf was blind, mydriatic and pupillary light reflexes were negative. The eyeballs were well developed. Jerk (slow-quick) nystagmus movements involving both eyes could be seen. Necropsy findings included cranium bifidum on the midline in the frontal area, through which brain tissue was visible, comparatively small cranial cavity and the hypoplasia of telencephalon (cerebral cortex, hippocampus, and striatum), diencephalon (globus pallidus, thalamus, hypothalamus, hypophysis), and mesencephalon. The cerebellum and caudal parts of the brainstem were present. The case was diagnosed as cranium bifidum and meningo-encephalocele.